Auf der Jagd nach der Sonne Das journalistische Feld und die Atomkraft in Japan - Weiß, Tobias (Studien zur Politischen Soziologie, 2019)
This book analyses the portrayal of nuclear power in Japanese journalism and the factors that influence it. Combining a field theoretical approach to journalism with frame analysis on different levels of the communication process, the author argues that the nuclear industry in Japan used its financial power to form a 'pro-nuclear civil society' and that this frame sponsorship is the reason for the relatively positive portrayal of nuclear power in Japan until 2011. After 'Fukushima', journalistic autonomy in this domain increased and journalism became a driving force of change in nuclear policy. At the same time, the field of journalism became polarised because its more heteronomous parts remained integrated into the 'pro-nuclear civil society'. This book offers a new perspective on the Japanese media and journalism in Japan, emphasising heterogeneity and change in contrast to previous research, which focused on press clubs as institutions of pervasive media control.